Contemporary Criminal Policy and Its Impact on the Development of Penal Law - Ass.lect Mayada Hussein Salman (Journal of College of Education, 2025)
Current developments in any country impose a complete review of its legal system in general and the penal system in particular, because the legislation in force may not be consistent with the contemporary stage that followed the previous stage. This development that follows that stage must be in line with the criminal policy adopted by the legislator in the areas of criminalization and punishment to achieve the optimal level of achieving the interest of the group and ensuring that the development keeps pace with the prevailing social values ​​that guarantee the state’s right to impose punishment, protect society from violations, and confront deviations and forms of behavior that disrupt the security and order of society. Therefore, the legislator may find himself facing a major task represented in reviewing all legislation that may conflict with the new conditions. In doing so, he takes legal paths that enable him to amend or abolish the legislation in force to be consistent with a modern criminal policy.
Keywords: criminal policy, social defense, penal law